Implementasi Metode RAD untuk Membangun Aplikasi Daur Ulang Sampah berbasis Android - Fatmariani, Fatmariani (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Abstract:Garbage is a leading problem polemic that always exists in the surrounding environment, with the amount of garbage the more pollution that causes disasters, one of which is flooding. Garbage itself is divided into organic waste and non-organic waste. Organic waste itself can be processed into compost, while non-organic waste can be recycled, one of which is handicrafts. The purpose of this research is to create an android-based application that is used to provide information and procedures for recycling waste. The method used is RAD, namely planning, design, and implementation. The results obtained in this study are an application that contains information that can be used by the community in recycling waste.